SISTEM PENGOLAHAN DATA PELAYANAN SERTIFIKASI TANAH BERBASIS WEB MENGGUNAKAN METODE WATERFALL PADA KANTOR KECAMATAN (STUDI KASUS : KECAMATAN RAJEG) - Laurensius Novian Bagas Setyawan; Niki Ratama (Journal of Research and Publication Innovation, 2023)
Services can be defined as all forms of services, both in the form of public goods and public services, which in principle are the responsibility of and are carried out by government agencies at the center, in the regions, and in the environment. Land Certification is the process of making a written or printed sign or statement (statement) given by the Land Deed Making Officer (PPAT). In the management of certificates or deeds through several stages at the District Office to be processed by the Land Deed Making Officer (PPAT). In the process of processing data for certificates or deeds in Rajeg District, it is still done manually by submitting the required file requirements and then carrying out an inspection by the official making the land deed, in this process it is still not effective because files can be lost or damaged. Then in the process of making the deed it is still semi-manual using a manual typewriter and the typing process takes a long time, and there is no system that can solve this problem. The purpose of this study is to provide convenience in the process of processing data and making sales and purchase deeds and grant deeds in the sub-district. The development of this research application system uses the waterfall method. In testing using a black box. This land certification service data processing system can help and simplify the process of filing deed, especially in data processing and printing of deed so that it is faster in the process of making deed. Keywords: Website, data processing, land certificate.